ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT JUDGMENT (Studi Kasus Pada Pemeriksa BPK Perwakilan Provinsi Jawa Tengah) - Nusabela, 11.05.52.0031; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to analyze the influence of experience on audit, audit expertise, understanding of the code of ethics, the complexity of the task, obedience pressure and time budget pressure on audit judgment on BPK Representatives of the Province of Central Java. The population of this research are all auditor who have followed Education and Training of Financial Possion of Auditor and 2 years minimal job experience as auditor on BPK. Sampling was counducted using a purposive sampling method and total ofÂ samples is 95 respondens. Primary data collection method used is multiple regresion model. The results showed that the skills audit significant positive effect on audit judgment, understanding the code of ethics is not a significant positive effect on audit judgment. Pressure and time budget pressure obedience significant negative effect on audit judgment. while the complexity of the task of auditing experience and significant negative effect on audit judgment.Keywords: Audit Experience, Audit Expertise, Ethics Orientation, Task Complexity, Obedience Pressure, Time Budget Pressure, Audit Judgment